E.B. O'Callaghan, Laws and Ordinances of New Netherland, 1638-1674, at 234-35 (1868); N.Y. Col. MSS, VIII 56 - (:unkn) unknown (My University, 1656)
Prohibited admission of "any Indians" in possession of a gun or other weapon into Fort Amsterdam or in the Flatland.
Keywords: CARRY - DANGEROUS PERSONS; ENSLAVED PERSONS & OTHER MINORITIES